2002
DOI: 10.1093/nar/gkf469
|View full text |Cite
|
Sign up to set email alerts
|

The human XPC DNA repair gene: arrangement, splice site information content and influence of a single nucleotide polymorphism in a splice acceptor site on alternative splicing and function

Abstract: XPC DNA repair gene mutations result in the cancer-prone disorder xeroderma pigmentosum. The XPC gene spans 33 kb and has 16 exons (82-882 bp) and 15 introns (0.08-5.4 kb). A 1.6 kb intron was found within exon 5. Sensitive real- time quantitative reverse transcription-polymerase chain reaction methods were developed to measure full-length XPC mRNA (the predominant form) and isoforms that skipped exons 4, 7 or 12. Exon 7 was skipped in approximately 0.07% of XPC mRNAs, consistent with the high information cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
119
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(130 citation statements)
references
References 37 publications
5
119
0
6
Order By: Relevance
“…Frequencies of the 499Val and IVS11-5A alleles among healthy Koreans were 0.712 and 0.391, respectively, which were similar to those (0.768 and 0.423, respectively) of NIH donors in the United States. 19,20 Frequencies of the PATþ and 939Gln alleles among healthy Koreans were 0.373 and 0.394, respectively, which were also similar to those of Caucasians (0.333 and 0.335, respectively). 21,25 In agreement with previous studies, 19,20,26 we found that the Val499Arg, PAT-/þ, IVS11-5C?A and Lys939Gln polymorphisms were in LD.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Frequencies of the 499Val and IVS11-5A alleles among healthy Koreans were 0.712 and 0.391, respectively, which were similar to those (0.768 and 0.423, respectively) of NIH donors in the United States. 19,20 Frequencies of the PATþ and 939Gln alleles among healthy Koreans were 0.373 and 0.394, respectively, which were also similar to those of Caucasians (0.333 and 0.335, respectively). 21,25 In agreement with previous studies, 19,20,26 we found that the Val499Arg, PAT-/þ, IVS11-5C?A and Lys939Gln polymorphisms were in LD.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, -449G?C and -371G?A polymorphisms were linked with these 4 polymorphisms. Khan et al 20 reported that haplotypes PAT-/ IVS11-5C/939Lys and PATþ/IVS11-5A/939Gln accounted for approximately 60% and 40%, respectively, of the chromosome among NIH donors. Frequencies of the haplotypes of these 3 polymorphisms among controls in the current study were comparable with their report.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations